Bold and small: using nanotechnology for magnetic filtration of an inorganic pigment liquid slurry - McRorie, Aaron H. (Kansas State University, 2018)
As a chemist who values purity of product, I have decided to look into various methods of filtration to ensure purity of final product. One such method is magnetic filtration of metallic impurities. For certain applications, the presence of ferromagnetic iron can increase magnetic susceptibility of certain items and therefore it must be removed selectively. One possible method of filtration that will bind much more selectively than a generic magnet is the use of nanoparticles. The following report is the research into what would be the best method of magnetic filtration using nanoparticles in a liquid slurry.
Keywords: Nanotechnology